Modern views on expanding of tissues, having own blood circulation, in reconstructive surgery of the burns consequences - О. А. Zhernov; G. P. Коzynetz; М. Кіtri (Клінічна хірургія)
Modern views on expanding of tissues, having own blood circulation, in reconstructive surgery of the burns consequences